O Tribunal Regional do Trabalho na cidade do Rio de Janeiro durante a ditadura civil-militar (1964-1979) - Silva, Claudiane Torres da (2015)
The purpose of this research is to think of the lawsuits filed by workers' unions in the city of Rio de Janeiro which included part of the jurisprudence of the Regional Labor Court of the First Region, observing the collective judgments made in the second instance of Labour Justice. Materials and legal dialogues found were observed in the collective judgments of the Regional Labor Court highlighting the main labor issues during the years 1964 and 1979 related to labor law in Brazil. With the chronological crop year 1964, when there was the coup that overthrew President João Goulart, until 1979 when the political détente process, we can see a change in the working class action in the context of the new unionism, the research also aims to analyze the performance of the labor judiciary agents during the civil-military regime observing the practice of labor judiciary on the political and economic project adopted in the civil-military regime that reached specifically the interests of workers.